The role of neurophysiological tools in the evaluation of ischemic stroke evolution: a narrative review - Francesco Motolese; Francesco Motolese; Jacopo Lanzone; Antonio Todisco; Antonio Todisco; Mariagrazia Rossi; Mariagrazia Rossi; Francesca Santoro; Francesca Santoro; Alessandro Cruciani; Alessandro Cruciani; Fioravante Capone; et al. (Frontiers in Neurology, 2023)
Ischemic stroke is characterized by a complex cascade of events starting from vessel occlusion. The term “penumbra” denotes the area of severely hypo-perfused brain tissue surrounding the ischemic core that can be potentially recovered if blood flow is reestablished. From the neurophysiological perspective, there are local alterations—reflecting the loss of function of the core and the penumbra—and widespread changes in neural networks functioning, since structural and functional connectivity is disrupted. These dynamic changes are closely related to blood flow in the affected area. However, the pathological process of stroke does not end after the acute phase, but it determines a long-term cascade of events, including changes of cortical excitability, that are quite precocious and might precede clinical evolution. Neurophysiological tools—such as Transcranial Magnetic Stimulation (TMS) or Electroencephalography (EEG)—have enough time resolution to efficiently reflect the pathological changes occurring after stroke. Even if they do not have a role in acute stroke management, EEG and TMS might be helpful for monitoring ischemia evolution—also in the sub-acute and chronic stages. The present review aims to describe the changes occurring in the infarcted area after stroke from the neurophysiological perspective, starting from the acute to the chronic phase.